Strategi Coping Masyarakat Miskin dalam Mengatasi Kelangkaan Air di Pulau Kecil Kabupaten Seram Bagian Timur, Maluku - Hahury, Hendri Dony; H Louhanapessy, Fredy; Rumalolas, Astari (Sodality: Jurnal Sosiologi Pedesaan, 2022)
This study aims to describe views on poverty through limited natural resources in the form of clean water scarcity and the coping strategies for the poor in overcoming it in rural areas on a small island. It took place in Rumeon Village, East Seram Regency, Maluku Province, Indonesia. This study was conducted using a qualitative method with a phenomenological approach. In-depth interviews, observations and documentations were used to collect data. The data was analyzed by following the steps proposed by Moustakes, and the source triangulation method was used to examine the data validity. The results showed that community had been suffering from water scarcity for a long time and had received no assistance. Factors causing the water scarcity included seawater contamination on the water sources, climatic and environmental changes, and population growth. The community attempted to overcome the clean water scarcity by utilizing resources available to them as a coping strategy applied including water harvesting and the use of alternative water sources. In addition, as a result of the long-standing condition of clean water scarcity in Rumeon Village, the community had to utilize the social and cultural values as an effort to overcome it so as to reduce the high cost and not to cause conflicts among them.